Did subsidies included in the 2009 Stimulus Package encourage enrolment in COBRA?. (15th December 2022) - Zimmer, David M.
Abstract: The 2009 Stimulus Package in the US introduced a 65 per cent subsidy for COBRA coverage for individuals who experienced employment separation between 1 September 2008 and 2 June 2010. This paper provides evidence that the subsidy led to statistically significant and non‐trivial increases in the probability that job separators enrolled in COBRA, but only among those who qualified for the subsidy. Specifically, the subsidy appears to have boosted the probability of COBRA enrolment among subsidy qualifiers by approximately 80 per cent. Among people who separated from jobs in manufacturing and business/professional services – two industries hit hard by the recession – the subsidy boosted enrolment probabilities among subsidy qualifiers by 60 per cent and 80 per cent, respectively.